R-matrix and Baxter Q-operators for the noncompact SL(N,C) invariant spin chain - Derkachov, S.É.; Manashov, A.N. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
The problem of constructing the SL(N,C) invariant solutions to the Yang-Baxter equation is considered. The solutions (R-operators) for arbitrarily principal series representations of SL(N,C) are obtained in an explicit form. We construct the commutative family of the operators Qk(u) which can be identified with the Baxter operators for the noncompact SL(N,C) spin magnet.